Relationship between quorum sensing and biofilm formation - Teo, Ling Yu (2016)
Biofilm formation, which is also known as biofouling, is an important issue in wastewater treatment as it can impede mass transfer of purification membrane system. Studies have shown that the biofilm formation is triggered by Quorum Sensing molecules produced by bacteria communities in the waste water. This project focus on examining the relationship between the concentration of quorum sensing molecules and biofilm formation, and to establish the function between amount of biofilm formation and the concentration of quorum sensing modules if such relationship is present. N-Acylhomoserine lactone (AHL) quorum sensing molecules was used to determine its effect on various type of microorganisms such Pseudomonas aeruginosa (PAO1), Escherichia coli (MG 1655), Sludge as well as Pseudomonas putida (KT 2440) at vary concentrations. Serial dilution was performed on AHL stock to prepare a wide range of concentration to study biofilm formation. M9 media and microorganisms as well as the diluted AHL stock will be added into the 96 wells of microtiter assay plate with 3 replicates for each microorganism. Assay is stained with 0.1% Crystal Violent solution and quantify using 30 % of acetic acid. Results can be obtained from spectrometer to measure the absorbance values at wavelength of 550nm. Addition of AHL signaling molecules does impact the biofilm formation in the 4 microorganisms. However, the relationship between AHL quorum sensing based and biofilm formation is still unclear. Future research should be conducted to validate the trends and behaviors of the AHL’s effect on biofilm formation.